Gene gain and loss and recombination shape evolution of Listeria bacteriophages of the genus Pecentumvirus - Blanco Fernandez, Maria Dolores (2020)
Listeria monocytogenes is an important food-borne pathogen and its bacteriophages are promising tools for its control in food and surfaces. Listeria bacteriophages belonging to the genus Pecentumvirus of the family Herelleviridae are strictly lytic, have a contractile tail and a large double stranded DNA genome (mean of 135.4 kb). We report the isolation and genome sequences of two new Pecentumvirus bacteriophages: vB_Lino_VEfB7 and vB_Liva_VAfA18. Twenty-one bacteriophages of this genus have been described and their genomes were used for the study of Pecentumvirus evolution. Analyses showed collinear genomes and gene gain and loss propensity and recombination events were distinctly found in two regions. A large potential recombination event (≈20 kB) was detected in P100 and vB_Liva_VAfA18. Phylogenetic analyses of multi-gene alignments showed that diversification events formed two groups of species distantly related.